Learning ServiceNow: Administration and Development on the Now Platform, for Powerful IT Automation - Woodruff, Tim (Packt Publishing, Limited, 2018)
ServiceNow is a powerful IT service management and automation platform that has made significant inroads in the Enterprise market due to its robust set of features and capabilities. This book will help you get started as a ServiceNow developer or administrator, and leverage the full capabilities of the ServiceNow platform through real-world.